IL CURRICULO VERTICALE E L’EDUCAZIONE LINGUISTICA : Contributi di Francesca Gallina, Emanuela Atz, Monica Barni, Annarosa Guerriero, Matteo La Grassa, Rosalia La Perna, Sergio Lubello, Claudio Nobili, Antonio Serradifalco, Erika Raniolo, Cecilia Varcasia (ItalianoLinguadue, 2025)
Monografia